KOMUNIKASI PEMERINTAHAN PEMERINTAH KOTA TANJUNGPINANG DALAM MEWUJUDKAN SMART BRANDING DI KOTA TANJUNGPINANG TAHUN 2019 – 2020 - Alysiah Nur Idriati Sa’ban; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
As a serious step in implementing e-government in Indonesia, Tanjungpinang City is accelerating development by utilizing information technology to develop Tanjungpinang smart city which includes the dimensions of smart branding. Of course, in realizing smart branding, the Tanjungpinang City Government has carried out various government communications to realize smart branding through various programs designed to realize smart branding. The purpose of this study is to find out how government communication is carried out by the Tanjungpinang City Government to realize smart branding and what are the factors that hinder government communication. The research approach used is a qualitative approach. This type of research is descriptive. The research location is in Tanjungpinang City, precisely in the offices of several stakeholders who are authorized to realize smart branding. The types and sources of research data are divided into primary and secondary data with data collection techniques through interviews and secondary data in the form of supporting data relating to the realization of smart branding. The results of this study are that government communication carried out by the Tanjungpinang City Government in realizing smart branding in Tanjungpinang City in 2019 - 2020 can be seen through four elements consisting of attribute, message, differentiation, and ambassadorship. However, the government communication seems ineffective because it has not been able to meet the indicators of the effectiveness of government communication from a professional perspective, namely the availability of formal rules, financial resources, and competent and skilled human resources. Keywords : Government Communication, Smart Branding, Local Government